Traditional usages of ichthyotoxic plant Barringtonia asiatica (L.) Kurz. by the Nicobari tribes - T. Ravikumar; Nagesh-Ram; S. Dam-Roy; P. Krishnan; Grinson-George; M. Sankaran; V. Sachithanandam (Journal of Marine and Island Cultures, 2015)
The Barringtonia asiatica is a medium size tree commonly found in Car Nicobar Island known for its ichthyotoxic property. It grows on sandy and rocky shore areas and has lantern shaped seeds, locally called Kinyav used during the calm season in shallow and low tide waters for killing fishes, octopus, etc. At every successful operation they harvest about 1–3 kg and on the whole about 10–20 kg of fishes per trip. This method of fish catching was popular among the Car Nicobari tribes until massive tsunami of 26th December, 2004, which caused dislocation of tribes from their erstwhile coastal inhabitations to interior areas, damage of coral reefs, permanent water intrusion in the intertidal area and destruction of Kinyav trees. Hence, now-a-days the popularity of this fishing method among them has diminished. The study not only reveals the usefulness of seeds in harvesting of fishes but also the utilization of other parts of tree such as leaves for therapeutic purpose in fracture, wound, de-worming, pain relieving of human beings; log for construction of canoe, wooden houses, sitting stage, handicraft items, fire wood and whole tree for preventing the coastal erosion.